2011
DOI: 10.1152/ajpregu.00316.2011
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive mechanisms to compensate for overnutrition-induced cardiovascular abnormalities

Abstract: In conditions of overnutrition, cardiac cells must cope with a multitude of extracellular signals generated by changes in nutrient load (glucose, amino acids, and lipids) and the hormonal milieu [increased insulin (INS), ANG II, and adverse cytokine/adipokine profile]. Herein, we review the diverse compensatory/adaptive mechanisms that counter the deleterious effects of excess nutrients and growth factors. We largely focus the discussion on evidence obtained from Zucker obese (ZO) and Zucker diabetic fatty (ZD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 42 publications
(74 citation statements)
references
References 120 publications
(145 reference statements)
2
71
0
1
Order By: Relevance
“…Interestingly, hyperinsulinemia-induced cardiac hypertrophy is accompanied by a reduction in AT 1 R, an increase in AT 2 R, and activation of S6K1 via the PI3K/Akt signaling pathway (61). The association between increases in AT 2 R protein and mTOR/S6K1 activation in insulin resistance-induced cardiac hypertrophy prompts us to posit that mTOR/S6K1-induced increases in translation could, in part, contribute to increases in AT 2 R protein levels (60).…”
Section: Effects Of the Raas On Mtor/s6k1 And Insulin Metabolic Signamentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, hyperinsulinemia-induced cardiac hypertrophy is accompanied by a reduction in AT 1 R, an increase in AT 2 R, and activation of S6K1 via the PI3K/Akt signaling pathway (61). The association between increases in AT 2 R protein and mTOR/S6K1 activation in insulin resistance-induced cardiac hypertrophy prompts us to posit that mTOR/S6K1-induced increases in translation could, in part, contribute to increases in AT 2 R protein levels (60).…”
Section: Effects Of the Raas On Mtor/s6k1 And Insulin Metabolic Signamentioning
confidence: 99%
“…Increased mTORC1-mediated translation underlies cardiac hypertrophy and is implicated in cardiovascular dysfunction. Meanwhile, cardiac overexpression of mTOR protects against cardiac dysfunction following left ventricular pressure overload through activation of AT 2 R, which provides a downstream cardioprotective compensatory servoregulatory mechanism (61).…”
Section: Pi3k/aktmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously proposed that compensative/adaptive mechanisms are activated in ZO rat heart that may have a role in attenuating the progression to diabetic cardiomyopathy in these animals compared to Zucker diabetic fatty rats [175] . Additionally, we have recently shown that miR-200c, an miRNA only modestly expressed in the heart, is increased in ZO rat heart, and this increase in miR-200c may serve as a compensatory mechanism to downregulate excessive activation of the nutrient sensor kinase S6K1 [176] .…”
Section: Mirna Regulation Of Apoptosismentioning
confidence: 99%
“…ACE2 have been described to be a potent negative regulator of RAS, counterbalancing the multiple functions of ACE, thus, it plays a protective role in the CV system and other organs [75] . Also, chronic activation of the RAS was shown to underlie HTN, insulin resistance, cardiac and renal disease, and polycystic ovarian syndrome and it serves as a link between obesity and low-grade systematic inflammation [76][77][78][79][80] . In addition, it is suggested that RAS contributes to the atherosclerotic process through angiotensin Ⅱ, which acts as a proinflammatory mediator directly inducing atherosclerotic plaque development and heart remodeling and exacerbate endothelial dysfunction [81,82] .…”
Section: Involvement Of the Renin-angiotensin System (Ras)mentioning
confidence: 99%